2019
DOI: 10.1002/ejhf.1492
|View full text |Cite
|
Sign up to set email alerts
|

Acute heart failure congestion and perfusion status – impact of the clinical classification on in‐hospital and long‐term outcomes; insights from the ESC‐EORP‐HFA Heart Failure Long‐Term Registry

Abstract: Aims Classification of acute heart failure (AHF) patients into four clinical profiles defined by evidence of congestion and perfusion is advocated by the 2016 European Society of Cardiology (ESC)guidelines. Based on the ESC‐EORP‐HFA Heart Failure Long‐Term Registry, we compared differences in baseline characteristics, in‐hospital management and outcomes among congestion/perfusion profiles using this classification. Methods and results We included 7865 AHF patients classified at admission as: ‘dry‐warm’ (9.9%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
173
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(202 citation statements)
references
References 33 publications
9
173
1
2
Order By: Relevance
“…To better address WASH rates, it will be necessary to dissect the profiles of congestion to distinguish between right‐ and left‐sided congestion, as recently reviewed by Thibodeau and Drazner . The European study identified tricuspid regurgitation as a prominent factor in persistent congestion . Patients with right ventricular failure and disproportionate right‐sided congestion are now well‐recognized to be at greater disadvantage from cardio‐renal limitations.…”
Section: Updating Profiles To Drive Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…To better address WASH rates, it will be necessary to dissect the profiles of congestion to distinguish between right‐ and left‐sided congestion, as recently reviewed by Thibodeau and Drazner . The European study identified tricuspid regurgitation as a prominent factor in persistent congestion . Patients with right ventricular failure and disproportionate right‐sided congestion are now well‐recognized to be at greater disadvantage from cardio‐renal limitations.…”
Section: Updating Profiles To Drive Therapymentioning
confidence: 99%
“…3 The European study identified tricuspid regurgitation as a prominent factor in persistent congestion. 6 Patients with right ventricular failure and disproportionate right-sided congestion are now well-recognized to be at greater disadvantage from cardio-renal limitations. We are only beginning to recognize the relationships between congestive hepatopathy, inflammation, malnutrition, and HF outcomes.…”
Section: Real-time Assessment Of Haemodynamic Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical profile of acute HF patients affects outcomes. 12 Chioncel et al 13 and Javaloyes et al 14 reported prevalence and prognostic impact of clinical phenotypes based on perfusion and congestion status. The phenotype 'wet-warm' was the most commonly observed.…”
Section: Clinical Phenotypes and Outcomesmentioning
confidence: 99%